INSTITUTIONAL OVERHEAD ON GOVERNMENT PROJECTS. - Devine, Carl Thomas (The Accounting Review, 1945)
Abstract All accountants are acutely aware of the difficulties surrounding the concept of cost, but doubtless many have not had the questionable opportunity of examining the special obstacles peculiar to nonprofit institutions. Since the accountant's expenditure approach to cost is highly objectionable, it may be that the economist's concept of cost can be employed. To economists and many businessmen cost is invariably associated with sacrifice. To this group it seems unreasonable for accountants to insist that interest paid for borrowed funds is a cost while the sacrifice of earnings from funds belonging to the enterprise is not considered cost. Accountants have parried these criticisms by pointing out the need for objective criteria for making entries and by showing that special calculations can be easily prepared for the comparatively rare instances when all economic costs must be included. But with regard to institutional costs it seems, at first sight, that the economic approach has a clear-cut superiority. Unfortunately, the economic concept of sacrifice is itself little, if any, better than the accountant's less sophisticated approach.